Chukotka’s Indigenous intellectuals and subversion of Indigenous activism in the 1990s - Gray, Patty (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThis paper, based on the author’s extensive field research in Chukotka in the 1990s, examines the conditions for Indigenous activism in Chukotka during the decade following the dissolution of the Soviet Union. The Indigenous movement in Chukotka faced extremely difficult conditions in the 1990s because of a concerted attack by a belligerent and chauvinistic regional administration that sought to undermine any effort on the part of Indigenous activists to mount an effective movement.